Penerapan Alat Ukur Tinggi Badan Otomatis Berbasis Arduino sebagai Inovasi Pelayanan Kesehatan Masyarakat Desa - Mutia Perwita Sari; Tatang Hidayatullah; Allauddin Al-Afghani; Waldi Sholistiawan (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
Height measurement is an important activity in community health services, particularly for growth monitoring and anthropometric data collection. However, manual height measurement processes often face challenges such as time inefficiency, potential reading errors, and inconsistent measurement results. This community service activity aims to implement an automatic height measurement device based on Arduino Uno and an ultrasonic sensor as a simple technological solution to support community health service activities during the Community Service Program (PENGABDIAN KEPADA MASYARAKAT) in Pringgasela Selatan Village. The implementation method includes device design, system assembly, functional testing, and direct application of the device in community service activities. The results show that the automatic height measurement device provides relatively consistent measurement results compared to manual methods and simplifies the measurement process by delivering quick and easily readable outputs. The application of this device also improves the efficiency of health service activities and supports the provision of more practical measurement data. Therefore, the Arduino-based automatic height measurement device can be utilized as a supporting tool for community health services using simple technology.